Village Poverty And Financial Performance Study Between The Land Area And The Archipelago In The District Of Sumenep - Madura - Bambang Haryadi; Aisyah Ariefiana (MediaTrend, 2021)
This study aims to describe the condition of financial performance and the level of village poverty in the mainland and island villages in Sumenep Regency. Then, this study will also examine the significance of differences in financial performance conditions and poverty levels between island and mainland villages. Next, test the correlation between the level of dependence of the village on the level of village poverty. The samples were selected randomly (random sampling) as many as 56 village governments. The analysis technique used is the Independent Sample T-test. The results showed that there was a very significant relationship or correlation between the level of dependency of the village and the level of village poverty. In addition, the results of the study indicate that there are differences in the financial performance of the mainland and archipelago village governments from the PADesa effectiveness ratio. Meanwhile, from the economic ratio, efficiency, village financial independence and village financial dependence, there is no difference in performance between the mainland and archipelago village governments. In terms of the ratio of village financial effectiveness, the mainland village government is superior to the archipelagic region.